Legal Policy and Environmental Justice in Indonesia’s Forest Area Enforcement - Eka Padmahantara Antonius; Sri Wahyu Handayani; Rahadi Wasi Bintoro (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Forest governance remains a significant legal and environmental challenge in Indonesia due to the widespread occurrence of illegal logging, unauthorized oil palm plantations, and unlicensed mining activities within forest areas. These practices have caused environmental degradation, reduced state revenues, and generated conflicts involving indigenous peoples and local communities. In response, the Indonesian government enacted Presidential Regulation Number 5 of 2025 concerning Forest Area Enforcement as a legal instrument to restore state control over forest areas and strengthen forest governance. However, concerns remain regarding the extent to which the regulation reflects environmental justice principles. This research aims to analyze the legal policy underlying state re-control of forest areas through Presidential Regulation Number 5 of 2025 and to evaluate its conformity with the principles of environmental justice. The study employs normative legal research using statutory and conceptual approaches. The study concludes that while Presidential Regulation Number 5 of 2025 strengthens state authority over forest governance and contributes to legal certainty, its implementation requires further legal reform to ensure the fulfillment of distributive, procedural, and social justice principles. Integrating environmental justice into forest area enforcement is essential for achieving sustainable and equitable forest governance in Indonesia.